Policy mixes for biodiversity: a diffusion analysis of state-level citizens’ initiatives in Germany - Tosun, Jale; Koch, Marcus (Journal of environmental policy and planning, 2021)
In 2018, a citizens’ initiative (CI) launched in the German State of Bavaria put forth the ‘policy idea’ of preserving and enhancing biodiversity and formulated a concrete policy proposal for implementing it. This policy idea diffused across Germany and resulted in the launch of similar CIs in the States of Baden-Württemberg, Brandenburg, Lower Saxony, and North Rhine-Westphalia. Research on policy diffusion through governmental channels has found that this process typically results in one of two outcomes: the policy in question is either adopted in a copy-and-paste manner or adapted to the respective local conditions. Did the diffusion process of the Bavarian CI result in the other CIs proposing a similar or different mix of policy goals and instruments? We find that the mix of policy goals corresponded closely to that of the Bavarian CI, suggesting diffusion through imitation or learning but with an element of adaptation as well. Striking differences exist between the mix of policy instruments employed by the Bavaria-based CI and the other CIs, which corroborates the importance of adaptation to local conditions.